DECT evaluation of noncalcified coronary artery plaque. Issue 10 (22nd September 2015) - Ravanfar Haghighi, Rezvan; Chatterjee, S.; Tabin, Milo; Sharma, Sanjiv; Jagia, Priya; Ray, Ruma; Singh, Rishi P.; Yadav, Rakesh; Sharma, Munish; Krishna, Karthik; Vani, V. C.; Lakshmi, R.; et al.
Abstract : Purpose: Composition of the coronary artery plaque is known to have critical role in heart attack. While calcified plaque can easily be diagnosed by conventional CT, it fails to distinguish between fibrous and lipid rich plaques. In the present paper, the authors discuss the experimental techniques and obtain a numerical algorithm by which the electron density ( ρe ) and the effective atomic number ( Z eff ) can be obtained from the dual energy computed tomography (DECT) data. The idea is to use this inversion method to characterize and distinguish between the lipid and fibrous coronary artery plaques. Methods: For the purpose of calibration of the CT machine, the authors prepare aqueous samples whose calculated values of ( ρe, Z eff ) lie in the range of (2.65 × 10 23 ≤ ρe ≤ 3.64 × 10 23 /cm 3 ) and (6.80 ≤ Z eff ≤ 8.90). The authors fill the phantom with these known samples and experimentally determine HU( V 1 ) and HU( V 2 ), with V 1, V 2 = 100 and 140 kVp, for the same pixels and thus determine the coefficients of inversion that allow us to determine ( ρe, Z eff ) from the DECT data. The HU(100) and HU(140) for the coronary artery plaque are obtained by filling the channel of the coronary artery with a viscous solution of methyl cellulose in water, containing 2% contrast. These ( ρe, Z eff ) values of the coronary artery plaque are used for their characterization on the basis of theoretical models of atomic compositions of the plaque materials. These results are compared with histopathological report. Results: The authors find that the calibration gives ρe with an accuracy of ±3.5% while Z eff is found within ±1% of the actual value, the confidence being 95%. The HU(100) and HU(140) are found to be considerably different for the same plaque at the same position and there is a linear trend between these two HU values. It is noted that pure lipid type plaques are practically nonexistent, and microcalcification, as observed in histopathology, has to be taken into account to explain the nature of the observed ( ρe, Z eff ) data. This also enables us to judge the composition of the plaque in terms of basic model which considers the plaque to be composed of fibres, lipids, and microcalcification. Conclusions: This simple and reliable method has the potential as an effective modality to investigate the composition of noncalcified coronary artery plaques and thus help in their characterization. In this inversion method, ( ρe, Z eff ) of the scanned sample can be found by eliminating the effects of the CT machine and also by ensuring that the determination of the two unknowns ( ρe, Z eff ) does not interfere with each other and the nature of the plaque can be identified in terms of a three component model.